Genotoxicity, cytotoxicity and gene expression in patients undergoing elective surgery under isoflurane anaesthesia - Braz, Mariana Gobbo [UNESP]; Mazoti, Marina Azer [UNESP]; Giacobino, Juliana [UNESP]; Braz, Leandro Gobbo [UNESP]; Golim, Marjorie de Assis [UNESP]; Ferrasi, Adriana Camargo [UNESP]; Carvalho, Lidia Raquel de [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Oxford University Press, 2011)
There are numerous studies reporting on the effects of inhalation anaesthesia in cells of exposed individuals but not much is known about the ability of isoflurane (ISF) to induce oxidative DNA damage. However, surgery is often associated with a temporary perioperative immunological alteration, and some volatile anaesthetics seem to contribute to a transient lymphocytopenia after surgery. We conducted a study to evaluate a possible genotoxic effect, including oxidative DNA damage, and apoptosis in peripheral lymphocytes of 20 patients American Society of Anaesthesiologists physical status I undergoing minor elective surgery lasting at least 120 min, under anaesthesia with ISF. We also investigated the expression of several genes in blood cells. Blood samples were collected at three time points: before anaesthesia (T(1)), 2 h after the beginning of anaesthesia (T(2)) and on the first post-operative day (T(3)). General DNA damage and oxidised bases (Fpg and endo III-sites) in blood lymphocytes were evaluated using the comet assay. Lymphocytes were phenotyped and apoptosis was evaluated by flow cytometry. In addition, expressions of hOGG1 and XRCC1, genes involved in DNA repair, and BCL2, a gene related to apoptosis, were assessed by quantitative real-time polymerase chain reaction. Results showed no statistically significant difference in the level of DNA damage and oxidised bases among the three sampling times. Anaesthesia with ISF did not increase the percentage of cells in early or late apoptosis in cytotoxic or helper T lymphocytes. Lower hOGG1 and BCL2 expressions were detected at T3 in comparison to the other two previous time points, and there was significantly lower expression of XRCC1 at T3 in relation to T2. In conclusion, the exposure to ISF did not result in genotoxicity and cytotoxicity in lymphocytes and in toxicogenomic effect in leukocytes, although DNA repair and apoptosis-related genes were down-regulated on the first post-operative day.